Implementation of smartphone-based experimental exercises for physics courses at universities. (11th February 2021) - Kaps, A; Splith, T; Stallmach, F
Abstract: A concept for undergraduate mechanics courses at universities is introduced where traditional pencil-paper based exercises are partially replaced by experimental exercises, in which smartphones are used as measurement devices. A detailed guidance for practical realization and implementation of these tasks formats into the course is presented. Three smartphone-based experimental exercises 'The tilting smartphone', 'The oscillation balance' and 'Using the Smartphone in a Torsion Pendulum' are presented. First empirical results with respect to the learning achievement indicate a mid size effect on the understanding of the physical concepts. Compared to the traditional pencil-paper based exercises, the students performance in the experimental exercises is slightly lower, although the motivation to solve these tasks is higher.